[PP.29.24] METABOLIC EFFECTS DIFFERENT BETA BLOCKERS DEPENDS ON PRESENTS INSULIN RESISTANCE IN PATIENTS WITH ARTERIAL HYPERTENSION AND METABOLIC SYNDROME. (September 2016) - Rekovets, O.; Sirenko, Y.; Torbas, O.; Primak, G.; Vaschylko, A.; Pavlyuk, E.; Savitskiy, S.; Sidorenko, P.; Polischuk, S.; Granich, V.; Kushnir, S.; Dobrokhod, A.
Abstract : Objective: To evaluate the changes of glucose, insulin, HOMA in patients with AH and MS during 6-month course of antihypertensive treatment with different beta blockers. Figure. No caption available. Design and method: Observed 131 patients with mild to moderate AH and MS (according ATP III criteria). Patients with diabetes mellitus were excluded. In 32 patients (1st group) treated by atenolol, 32 patients (2nd group) - bisoprolol, 32 patients (3rd group) - by carvedilol, 35 patients (4th group) – by nebivolol. In all patients before and after 6 month of therapy performed ABMP and OGTT estimation of HOMA. We divided patients in groups depends on presents or absents insulinresistance (HOMA>3 or HOMA<3). Results: The office BP and ABPM BP control was absolutely equivalent in all groups. At the end of the study decreased ABPM BP on 16, 86, 16, 26, 15, 40, 17, 00 mmHg respectively in groups, (p > 0, 05 between all groups). We analyzed glycemic control in the subgroup of patients depended of HOMA level (see table). * - p < 0, 05 between before and after treatment in atenolol subgroup # - p < 0, 05 between before and after treatment in carvedilol subgroup $ - p < 0, 05 between before and after treatment in bisoprolol subgroup £ - p < 0, 05 between before and after treatment in nebivolol subgroup ¥ - p < 0, 05 between nebivolol and atenolol subgroup (HOMA < 3) after treatment A – p < 0, 05 between carvedilol and atenolol subgroup (HOMA<3) after treatment ^ – p < 0, 05 between bisoprolol and atenolol subgroup (HOMA<3) after treatment Q – p < 0, 05 between nebivolol and carvedilol subgroup (HOMA<3) after treatment μ - p < 0, 05 between carvedilol and bisoprolol subgroup(HOMA<3) after treatment © - p < 0, 05 between carvedilol and bisoprolol subgroup (HOMA>3) after treatment W - p<0, 05 between nebivolol and atenolol subgroup (HOMA>3) after treatment R - p < 0, 05 between carvedilol and atenolol subgroup (HOMA>3) after treatment N – p < 0, 05 between bisoprolol and atenolol subgroup (HOMA>3) after treatment Conclusions: The 6-month therapy in patients with AH and MS with insulinresistance (HOMA>3) by atenolol can significantly worse HOMA, fasting insulin; patients with insulinresistance treated by bisoprolol, carvedilol and nebivolol decreased HOMA, fasting insulin. Different beta-blockers had different metabolic effects.